Percepciones estudiantiles sobre los portafolios digitales en Inglés con Fines Específicos - López Estrada, Patricia (2019)
A description is provided of the constructivist insights of four student populations using digital portfolios in a reading comprehension course. The results highlight the use of Google Docs as a digital platform to create two digital portfolios: a Reading Comprehension Portfolio (specific techniques) and a Vocabulary Portfolio (technical glossaries with agronomic jargon). They served as pedagogical tool to challenge students to participate in their own learning process and interact dynamically in a technological setting.